Experimental and numerical investigation of twin vertical axis wind turbines with a deflector. (1st April 2020) - Jiang, Yichen; Zhao, Peidong; Stoesser, Thorsten; Wang, Kun; Zou, Li
Highlights: A rhombus deflector improves the performance of a pair of counter-rotating vertical axis wind turbines. The wind turbine power output increases about 38.6% at low tip speed ratios. The wind turbines performance depends on the rotational directions and deflector position. The deflector accelerates flow velocity and restrains flow separation on the blade. Abstract: In this paper we report on the design and testing of a novel vertical axis wind turbine (VAWT) system. The system consists of two counter-rotating VAWT rotors and a deflector that is placed between the two rotors. The system's performance is first quantified in wind tunnel experiments and subsequently, three-dimensional computational fluid dynamics (CFD) simulations are performed to complement the experiments and to provide the fluid mechanical details. It is found that the deflector has a significant effect (power-increasing) on the power output of the two rotors, which is related to the rotational direction of the two rotors. With the addition of the deflector, the twin VAWT is able to harness up to 38.6% more wind energy compared with the system without deflector. The analysis of the CFD-produced flow field showed that the increased power output is the result of local acceleration of the fluid and local blockage effect of the deflector. The use of a deflector is found to be a simple and practical approach to improve the performance of twin VAWT system.